Pengaruh Work Overload, Stres Kerja dan Motivasi Kerja terhadap Turnover Intention: Studi pada Karyawan bagian Operator Produksi Sewing computer PT Hwaseung Indonesia - Fitrya Wulandari; Kiswoyo Kiswoyo; Mutmainah Mutmainah (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
This study aims to determine the effect of work overload, work stress, and work motivation on the turnover intention of employees at PT HWI's sewing computer production operators. The study utilizes three independent variables (endogenous), namely work overload, work stress, and work motivation, and one dependent variable (exogenous), turnover intention. The population in this study consisted of employees in the sewing computer section at PT HWI, with 99 respondents sampled for analysis. The results of the data analysis indicate that the indicators are valid and reliable. The classical assumption test showed no multicollinearity in the data. In the hypothesis testing, the variables of work overload, work stress, and work motivation were found to have no significant effect on turnover intention. These findings suggest that while work overload, stress, and motivation play important roles in employee well-being, they do not significantly impact the intention to leave the organization at PT HWI. Future studies could explore other factors influencing turnover intention and the dynamics between these variables.